The Role of Professional Ethics in Improving the Quality of Prospective Teacher Students - Feby Cahaya Hasibuan; Dinda Syahfitri; Hasyim (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the context of education, the ethics of the teaching profession include standards of behavior that must be adhered to by prospective teachers during education. The ethics profession plays an important role in shaping the character of a student, guiding them in the ethical decision-making process, developing positive interpersonal relationships, and being a model of good behavior for students. Professional ethics also provide a reference in professional systems and valkatsiyon. This research was conducted using a qualitative approach and literature study, with a population of Medan State University students. Data was collected through interviews using a question and answer technique. The results of the research showed that professional ethics have a role in the ethical and moral attitudes of prospective teachers. Professional ethics education in tertiary institutions will receive prospective teachers with character in the future. In the context of education, the ethics of the teaching profession include standards of behavior that must be upheld by teachers, prospective teachers who are currently studying.